The essential role of electron microscopy in the diagnosis of collagen type III glomerulopathy superimposed with membranous nephropathy or diabetic nephropathy - Fangcheng Zhang; Qi Shen; Xiaoling Sun; Xiao Long; Dan Cheng (BMC Nephrology)
Abstract Background Collagen type III glomerulopathy (CG) is a rare idiopathic nephropathy characterized by the massive deposition of dense, fractured, curved, band-like fibers in the mesangial and subendothelial regions. Ultrastructural pathological examination confirms that these deposits are composed of type III collagen. Here, we report two rare cases of CG: Patient I was superimposed with membranous nephropathy (MN), and Patient II was superimposed with diabetic nephropathy (DN), both confirmed by transmission electron microscopy (EM). Case presentation Both patients presented with bilateral lower extremity edema of unknown etiology. Patient I was admitted to the hospital multiple times due to persistent proteinuria. The phospholipase A2 receptor (PLA2R) test was positive, but there was no response to steroid treatment. Patient II has a 10-year history of hypertension and fasting hyperglycemia. Renal biopsies revealed segmental aggregation of homogeneous substances beneath the mesangium and endothelial cells. To obtain a definitive diagnosis, biopsy specimens were transferred to our department for electron microscopic evaluation. Conclusion This study highlights the ultrastructural characteristics of CG and emphasizes the indispensable role of electron microscopy in the diagnosis of CG, particularly when coexisting with other glomerular diseases. The Early EM examination in renal biopsies is crucial for a clear diagnosis and prognosis prediction.